2012
DOI: 10.1159/000343257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-9 Activity following Hypoxic Ischemia in the Developing Brain Using a Highly Specific Inhibitor

Abstract: Perinatal hypoxic ischemic (HI) brain injury is a leading cause of long-term neurological handicap in newborn babies. Recently, excessive activity of matrix metalloproteinases (MMPs), and in particular MMP-9, has been implicated in the aetiology of HI injuries to the immature brain. Our previous study suggested that MMP-9 may be involved in the development of the delayed injury processes following HI injury to the developing brain. Given this, we therefore propose that MMP-9 may be a useful target for rescue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…Specific inhibitor of MMP-9, SB-3CT has come forth with desirable properties of crossing blood brain barrier and therapeutic effects for treating neurological diseases due to inflammation [10]. This inhibitor has been studied for ischemia of immature brain and found to work efficiently; showing its utility in pediatric cases [11]. In this study, role of MMP-9 has been evaluated in progression of TBM.…”
Section: Introductionmentioning
confidence: 99%
“…Specific inhibitor of MMP-9, SB-3CT has come forth with desirable properties of crossing blood brain barrier and therapeutic effects for treating neurological diseases due to inflammation [10]. This inhibitor has been studied for ischemia of immature brain and found to work efficiently; showing its utility in pediatric cases [11]. In this study, role of MMP-9 has been evaluated in progression of TBM.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible for example that detrimental effects of MMPs such as myelin disruption, processing of other death pathway molecules and alteration of the extracellular matrix [50,51] may not be observed in vitro. Nevertheless, we have previously reported that SB-3CT was not neuroprotective after hypoxia-ischaemia in postnatal day 21 rats, consistent with a limited role of gelatinases in secondary inflammatory damage of the developing brain [52]. …”
Section: Discussionmentioning
confidence: 61%
“…18 This also was indicated by an investigation carried out by Ranasinghe and colleagues. 48 In their study, significant inhibition of brain pro-MMP-9 activity after hypoxic ischemia was observed by SB-3CT. Similar phenomena was observed in TBI models that increase in the pro-MMP-9 level was also observed in the lesioned cortex within 24 h after TBI in addition to the up-regulation of activated MMP-9.…”
Section: Effect Of Sb-3ct On Tbi Prognosismentioning
confidence: 93%
“…However, it is interesting to find that significant loss of behavioral deficit caused by acute neuro-degeneration and neuronal loss also was lessened by SB-3CT post-treatment. Similar administration was shown to be effective in inhibiting MMP activity in adult rat models of spinal cord injury 52 and ischemia 17 without any confounding toxic effects. Moreover, it was also demonstrated that apoptotic cell death within the hippocampus was significantly reduced, and the presence of immature neurons was significantly increased if acute post-intervention was carried out after TBI.…”
mentioning
confidence: 86%
See 1 more Smart Citation